Teaching physics laboratory skills' mastery at high school by fourth year students at the Faculty of Education Sana'a University - Dawood A. AL-Hidabi; Mohamed AL-Mekhlafi (University of Science and Technology, Yemen, 2009)
Teaching physics laboratory skills' mastery at high school by fourth year students at the Faculty of Education Sana'a University   The study aimed at investigating the level of mastery of 4th year students at the faculty of education, Sana'a University for teaching physics laboratory skills required at high school in Yemen.   First, researchers analysed the content of high school physics textbooks to identify the physics laboratory skills needed for teaching physics in high school. 86 skills were identified and categorized in 9 dimensions. Then, an observation schedule was developed for the top 10 identified laboratories skills. 40 male and female 4th year students were selected as stratified sample for investigating their mastery of physics laboratory skills by adopting the developed observation schedule. The results showed that the 4th year students' mastery of physics laboratory skills were low. Also, it was found that there is a positive correlation between students' physics achievement and their laboratory skills' mastery. Finally, the results showed that there is no significant differences between the mastery of all skills in general and each particular skills.   Several recommendations and suggestions were given at the end of the research report.